An inducible gene from glycoside hydrolase one family of Plutella xylostella decreases larval survival when feeding on host plant - Chen, Wei; Dong, Yuhong; Zheng, Ling; Lai, Yingfang; Li, Feifei; Zhou, Li; Wang, Beibei; You, Minsheng; He, Weiyi (Frontiers in Physiology, 2022)
Glycoside hydrolase family 1 (GH1) members exhibit a broad substrate spectrum and play important roles in insect-plant interactions, such as the defensive β-glucosidase and β-thioglucosidase (so-called myrosinase). However, knowledge about the expression profiling and function of GH1 members in a specialist pest of crucifers Plutella xylostella is still limited. In this study, 13 putative GH1 members of P. xylostella were identified based on the sequence characteristics, while no myrosinase activity was detectable in P. xylostella using gas chromatography-mass spectrometry (GC-MS). Expression profiling of these GH1 members identified the midgut-specific gene Px008848 that is induced by host plant. Further experiments revealed that the in vitro expressed Px008848 protein had β-glucosidase activity and the survival rate of the larvae feeding on wounded Arabidopsis thaliana leaves declined when leaves were treated with purified Px008848 protein. When CRISPR/Cas9-based homozygous mutant larvae of Px008848 and wild-type larvae were respectively transferred onto the A. thaliana, the larval survival rate of the mutant larvae was significantly higher than that of the wild-type individuals. Our work showed that certain insect GH1 gene may have negative effect on the development of larvae feeding on the host plant, which broadened our understandings on the evolutionary function of this gene family in the insect-plant interaction.